Genetic diversity of Plasmodium falciparum isolates from naturally infected children in north-central Nigeria using the merozoite surface protein-2 as molecular marker (2013)
Objective: To characterize the genetic diversity of Plasmodium falciparum (P. falciparum) field isolates in children from Lafia, North-central Nigeria, using the highly polymorphic P. falciparum merozoite surface protein 2 (MSP-2) gene as molecular marker. Methods: Three hundred and twenty children were enrolled into the study between 2005 and 2006. These include 140 children who presented with uncomplicated malaria at the Dalhatu Araf Specialist Hospital, Lafia and another 180 children from the study area with asymptomatic infection. DNA was extracted from blood spot on filter paper and MSP-2 genes were genotyped using allele-specific nested PCR in order to analyze the genetic diversity of parasite isolates. Results: A total of 31 and 34 distinct MSP-2 alleles were identified in the asymptomatic and uncomplicated malaria groups respectively. No difference was found between the multiplicity of infection in the asymptomatic group and that of the uncomplicated malaria group (P>0.05). However, isolates of the FC27 allele type were dominant in the asymptomatic group whereas isolates of the 3D7 allele type were dominant in the uncomplicated malaria group. Conclusions: this study shows a high genetic diversity of P. falciparum isolates in North-central Nigeria and is comparable to reports from similar areas with high malaria transmission intensity.